The six "ins" of climate-smart agriculture: Inclusive institutions for information, innovation, investment, and insurance - Meinzen-Dick, Ruth S.; Bernier, Quinn; Haglund, Eric (International Food Policy Research Institute, 2013)
This paper reviews the central role of institutions for climate-smart agriculture (CSA), focusing on the role of institutions in promoting inclusivity, providing information, enabling local level innovation, encouraging investment, and offering insurance to enable smallholders, women, and poor resource-dependent communities to adopt and benefit from CSA. We discuss the role of state, collective action, and market institutions at multiple levels, with particular attention to the importance of local-level institutions and institutional linkages across levels.